Initial Reports of the Deep Sea Drilling Project 1984
DOI: 10.2973/dsdp.proc.77.108.1984
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Diagenetic Models for Cretaceous Talus Deposits, Deep Sea Drilling Project Site 536, Gulf of Mexico

Abstract: Talus deposits recovered from Site 536 show evidence of aragonite dissolution, secondary porosity development, and calcite cementation. Although freshwater diagenesis could account for the petrographic features of the altered talus deposits, it does not uniquely account for isotopic or trace-element characteristics. Also, the hydrologic setting required for freshwater alteration is not easily demonstrated for the Campeche Bank. A mixing-zone model does not account for the available trace-element data, but does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…The type B clasts in Unit IV are similar to those at the foot of the Campeche Escarpment reported by Halley et al (1984). They interpreted the moldic porosity to have formed in deep wa ter by selective leaching of aragonite.…”
Section: Discussionsupporting
confidence: 74%
“…The type B clasts in Unit IV are similar to those at the foot of the Campeche Escarpment reported by Halley et al (1984). They interpreted the moldic porosity to have formed in deep wa ter by selective leaching of aragonite.…”
Section: Discussionsupporting
confidence: 74%
“…The best data for this stratigraphic level comes from the DSDP site 538A and EXXON well 3, both of which indicate evidence of clay, silts and calcareous muds Halley et al, 1984).…”
Section: Coastall Plain Wells the Eocene Guayabal Formationmentioning
confidence: 99%
“…This is a potential petroleum prospect several tens of kilometres wide and many thousands of kilometres long. Prolific production is established in the Poza Rica and Reforma trends (Enos, 1985;Viniegra, 1981 ;Aguayo et al, 1985) and secondary porosity is reported from the slope east of the Yucatan shelf (Halley et al, 1984). All portions of this trend will clearly not be equally prospective, but if zones of former discharge of meteoric water into the sea can be identified, these should be explored with particular care.…”
Section: Discussionmentioning
confidence: 99%
“…The Tamabra Limestone (Mid-Cretaceous, Albian and Cenomanian) of the Poza Rica trend, Mexico, will ultimately produce more than 2.3 x lo9 barrels of oil, largely from secondary porosity in probable basinmargin mass-flow deposits (Enos, 1977a(Enos, , 1985. Clarifying and quantifying the evolution of pore space in this type of reservoir has implications for development of this trend and other comparable deposits (Cook & Mullins 1983;Enos & Moore 1983;Halley, Pierson & Schlager, 1984;Hobson, Caldwell & Toomey, 1985;Crevello & Harris, 1985;Enos, 1977b).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation